Towards technology-based education: Exploration of augmented reality in e-modules for latest learning - Anggela Pratama; Moch Najril; Namira Khosyi (Himpunan Pengembang Kurikulum Indonesia, 2024)
Education is an important foundation for character development and improving the quality of human resources. In the ever-evolving landscape of classroom learning, teachers play an important role as facilitators in creating innovative and student-centered learning environments. This research explores the integration of Augmented Reality (AR) into E-Modules as innovative digital teaching materials. This research uses a literature review approach to explore the role of AR in developing interactive e-modules, which aims to increase student engagement and understanding regarding abstract concepts in learning. This research collects data from relevant research results, emphasizing the role of e-modules and AR in adapting to the era of digitalization. The findings show a significant positive impact of using AR in learning, reflected in an increase in student interest by 94 percent and an increase in understanding of the material by 90 percent. In addition, aspects such as appearance components and feasibility received positive responses of 88 percent and 84 percent respectively. This research shows that the integration of AR into the E-Module has a positive effect on student participation and understanding. The positive response from students highlights the potential of AR in creating an engaging learning process. Abstrak Pendidikan merupakan landasan penting bagi pengembangan karakter dan peningkatan kualitas sumber daya manusia. Dalam lanskap pembelajaran di kelas yang terus berkembang, guru memainkan peran penting sebagai fasilitator dalam menciptakan lingkungan pembelajaran yang inovatif dan berpusat pada peserta didik. Penelitian ini bertujuan untuk mengeksplorasi integrasi Augmented Reality (AR) ke dalam E-Modul sebagai bahan ajar digital inovatif. Pendekatan tinjauan literatur digunakan untuk mengeksplorasi peran AR dalam pengembangan e-modul interaktif yang bertujuan untuk meningkatkan keterlibatan peserta didik dalam pembelajaran dan pemahamannya mengenai konsep-konsep abstrak dalam pembelajaran. Penelitian ini mengumpulkan data dari hasil penelitian yang relevan, menekankan peran e-modul dan AR dalam beradaptasi dengan era digitalisasi. Temuannya menunjukkan adanya dampak positif yang signifikan penggunaan AR dalam pembelajaran, tercermin dari peningkatan minat peserta didik sebesar 94 persen dan peningkatan pemahaman materi sebesar 90 persen. Selain itu, aspek seperti komponen tampilan dan kelayakan mendapat respons positif masing-masing sebesar 88 persen dan 84 persen. Penelitian ini menunjukkan bahwa integrasi AR ke dalam E-Module berpengaruh positif terhadap partisipasi dan pemahaman peserta didik. Respons positif dari peserta didik menyoroti potensi AR dalam menciptakan proses pembelajaran yang menarik. Kata Kunci: augemented reality; pendidikan; e-modul; pembelajaran